Patient selection may affect gene therapy success. Dominant negative effects observed for ornithine transcarbamylase in mouse and human hepatocytes. - Morsy, M A; Zhao, J Z; Ngo, T T; Warman, A W; O'Brien, W E; Graham, F L; Caskey, C T (The Journal of Clinical Investigation, 1996)
We have achieved significant improvement of ornithine transcarbamylase deficiency (OTCD) in a mouse model through adenoviral-mediated gene transfer of the human ornithine transcarbamylase cDNA. Substantial reduction in orotic aciduria was observed within 24 h of treatment. Metabolic correction was later associated with phenotypic correction and moderate increase in enzymatic activity. In an effort to identify the level of gene expression required to achieve wild-type levels of enzyme activity we uncovered a dominant negative effect of the endogenous mutant protein on the activity of the delivered recombinant wild-type protein. This phenomenon is relevant to homomultimeric protein defects such as OTCD, represent a challenging category of disorders for gene therapy. Thus, although our findings indicate that adenoviral-mediated gene transfer may have potential as a short-term treatment for OTCD in humans and may be effective especially during catabolic crisis, the observations in this study suggest that careful patient selection based on mutation class may be essential for initial OTCD gene therapy trials, and perhaps, for other homomultimeric enzyme deficiencies being considered as gene therapy targets.